The district clerk and the 'man-leopard murders': Mediating law and authority in colonial Nigeria - Pratten, D (University of Wisconsin Press, 2006)
By uncovering the role of such men (and a few women) in the construction, function, and legal apparatus of colonial states, the essays in this volume highlight a new perspective.